2020
DOI: 10.3389/fspor.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Return to Sport Transition After ACL Injury: An Alpine Ski Racing Case Study

Abstract: Alpine ski racing is an extreme sport and ski racers are at high risk for ACL injury. ACL injury impairs neuromuscular function and psychological readiness putting alpine skiers with ACL injury at high risk for ACL reinjury. Consequently, return to sport training and testing protocols are recommended to safeguard ACL injured athletes against reinjury. The aim of this paper was to present a real-world example of a return to sport training plan for a female elite alpine ski racer who sustained an ACL injury that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 40 publications
0
65
0
Order By: Relevance
“…Given that high-intensity intermittent activity requires accelerations, change of direction and decelerations to be performed with maximal force almost instantaneously through competition (Ritchie et al, 2016;Jennings et al, 2010), RSI is a particularly important attribute for team sport athletes. Furthermore, it has been shown that in athletes who have suffered significant lower limb injures that the ability to produce force quickly is often attenuated in both the acute rehab and post return to play period (Read et al, 2020;Jordan et al, 2020). Thus, the current results present a useful method of within resistance training session organisation that can augment RSI for concurrently trained athletes such as team sport athletes.…”
Section: Discussionmentioning
confidence: 78%
“…Given that high-intensity intermittent activity requires accelerations, change of direction and decelerations to be performed with maximal force almost instantaneously through competition (Ritchie et al, 2016;Jennings et al, 2010), RSI is a particularly important attribute for team sport athletes. Furthermore, it has been shown that in athletes who have suffered significant lower limb injures that the ability to produce force quickly is often attenuated in both the acute rehab and post return to play period (Read et al, 2020;Jordan et al, 2020). Thus, the current results present a useful method of within resistance training session organisation that can augment RSI for concurrently trained athletes such as team sport athletes.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, it has been shown that in athletes who have suffered significant lower limb injures that the ability to produce force quickly is often attenuated in both the acute rehab and post return to play period (37,38). Thus, the current results present a useful method of within resistance training session organisation that can augment RSI for concurrently trained athletes such as team sport athletes.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, at Week 17 despite modest deficits in jump height (5%) and peak power (7%), relative to pre-injury, suggestive of performance decline secondary to the injury/deconditioning, there were substantial improvements in strategy/kinetic variables such as eccentric deceleration RFD (20%), concentric impulse-100 (8%) and lower limb stiffness (13%), indicative of improved SSC ability. 11 36 Importantly, at this time point, the player had achieved 97% of pre-injury maximal speed ( figures 4 and 6 ), without full recovery of aspects of neuromuscular performance, and several weeks remained before expected return to competition to further recover these.…”
Section: Progressing To On-pitch Rehabilitationmentioning
confidence: 90%
“…These data highlight both the importance of evaluating RFD-related variables following injury and of having healthy benchmark values to reduce the dependence on %ILA as a marker of status and progress. 11 12 …”
Section: Mechanical Loading and Rtsmentioning
confidence: 99%